Bacillus amyloliquefaciens FH-1 significantly affects cucumber seedlings and the rhizosphere bacterial community but not soil - Jingjing Wang (Nature Portfolio, 2021)
Abstract Plant growth-promoting bacteria (PGPB) inoculants have been applied worldwide. However, the ecological roles of PGPB under different soil conditions are still not well understood. The present study aimed to explore the ecological roles of Bacillus amyloliquefaciens FH-1 (FH) on cucumber seedlings, rhizosphere soil properties, and the bacterial community in pot experiments. The results showed that FH had significant effects on cucumber seedlings and the rhizosphere bacterial community but not on soil properties. The FH promoted cucumber seedlings growth, reduced the rhizosphere bacterial diversity, increased Proteobacteria, and decreased Acidobacteria. Linear discriminant analysis (LDA) effect size (LEfSe) revealed that FH enriched two taxa (GKS2_174 and Nannocystaceae) and inhibited 18 taxa (mainly Acidobacteria, Actinobacteria, BRC1, Chloroflexi, Plantctomycetes, and Verrucomicrobia). Co-occurrence network analysis demonstrated that FH increased bacteria-bacteria interactions and that Bacillus (genus of FH) had few interactions with the enriched and inhibited taxa. This might indicate that FH does not directly affect the enriched and inhibited taxa. Correlation analysis results displayed that cucumber seedlings’ weight and height/length (except root length) were significantly correlated with the 18 inhibited taxa and the enriched taxa Nannocystaceae. It was speculated that FH might promote cucumber seedling growth by indirectly enriching Nannocystaceae and inhibiting some taxa from Acidobacteria, Actinobacteria, BRC1, Chloroflexi, Plantctomycetes, and Verrucomicrobia.